2019
DOI: 10.1080/10826084.2019.1573836
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage from college drinking: A conceptual framework for alcohol’s harms to others among US college students

Abstract: Background: A growing literature shows that drinkers can harm bystanders through alcoholrelated harms to others (HTO). The burden of HTO is particularly consequential in college environments, where heavy alcohol consumption and related harms are highly prevalent. A key limitation to the current literature on HTO among college students is that the determinants of HTO in college settings are not well-described.Objective: This article presents an evidence-and theory-based conceptual framework of HTO among United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Participants also noted the impact of alcohol use on overall GPA, reinforcing the work of . Participants shared a range of ways in which students experienced harm as a result of others' use, including injury, fire alarms, disrupted sleep, and property damage, supporting the work of other researchers who found that 47-84% of students experienced secondary harms (e.g., Beckhoff et al, 2022;Trangenstein et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Participants also noted the impact of alcohol use on overall GPA, reinforcing the work of . Participants shared a range of ways in which students experienced harm as a result of others' use, including injury, fire alarms, disrupted sleep, and property damage, supporting the work of other researchers who found that 47-84% of students experienced secondary harms (e.g., Beckhoff et al, 2022;Trangenstein et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Heavy episodic drinking among college students is associated with diminished academic performance, cognitive deficits, sexual assault, and unsafe sex (White & Hingson, 2013). In addition to direct consequences, more than half of college students report having been harmed by others' drinking (Trangenstein et al, 2019). College drinking patterns result from the dynamic interplay of several systems, including government, business forces, and the college environment itself (Apostolopoulos et al, 2018).…”
Section: > > Backgroundmentioning
confidence: 99%
“…There are emerging discussions about collateral damage, external burdens (externalities), and harm to others. Focusing on costs and consequences in terms of harm to others, college students report experiencing harm as a result of others' drinking at rates ranging from 59% to 85% (Trangenstein, Wall, & Jernigan, 2019). Harm includes a number of unwanted consequences from nuisances such as loud parties to more serious violations such as interpersonal violence.…”
Section: Risks and Consequencesmentioning
confidence: 99%
“…Instead there is basic information available on living situations. For instance, college students living with a heavy drinker are 3.7 times more likely than their peers to experience harm over the course of a year (Trangenstein et al, 2019). Cabalatungan and McCarthy (2015) studied the relationship between other people' s drinking and college students' educational experiences.…”
Section: Risks and Consequencesmentioning
confidence: 99%